Assessing Occupational Stress in Seafaring: A Fuzzy Delphi Approach to Develop Effective Management Strategies in Offshore Support Vessel Operations - Othman, Rosni; Faizal, Harith; Jeevan, Jagan (Transactions on Maritime Science, 2023)
The maritime industry has long been a crucial component of Malaysia's economy. Seafarers in this industry face unique psychosocial, work-related, and environmental stressors, which can negatively impact their health, safety, and well-being. The operations of offshore support vessels (OSVs) are particularly hazardous and require effective strategies for occupational stress management. The Fuzzy Delphi method was used to identify the key enablers of occupational stress in OSV operations. The study has found that the main enablers of occupational stress in seafaring include vulnerability towards occupational hazards and risks, human capital skills, onboard living conditions, governance capacity, and mental burnout. These findings can help guide efforts to address the occupational stressors faced by seafarers serving on OSVs and enhance their working conditions, skills, and health. Shipping companies, policymakers, and organisations must collaborate to ensure the compliance with marine regulations and standards, improve shift schedules, and implement proper mechanisms to maintain the occupational health of seafarers during and post the Covid-19 pandemic.